Diverse Inter-Annual Variations of Winter Siberian High and Link With Eurasian Snow in Observation and BCC-CSM2-MR Coupled Model Simulation - Sun, Chenghu; Zuo, Jinqing; Shi, Xiaohui; Liu, Xiangwen; Liu, Haiwen (Frontiers in Earth Science, 2021)
Observational study illustrates that three distinct modes of winter Siberian high exist in observations at inter-annual time scale. In this paper, we compare connection between these diverse Siberian high modes with pre-autumn and simultaneous Eurasian snow cover in observation and BCC-CSM2-MR coupled climate model run under pre-industrial conditions from the CMIP6 project. Our analyses indicate that the inter-annual variation of observed Siberian high modes do have connection with pre-autumn and simultaneous Eurasian snow cover anomalies, but the BCC-CSM2-MR coupled climate model do not well capture the observed diverse Eurasian snow–Siberian high relationships. The BCC-CSM2-MR coupled climate model can partly reproduce the observed Siberian high modes, but fail to capture the spatial distribution and statistics of boreal fall and winter Eurasian snowpack, which is a key facet of simulated diverse Siberian high variability irrespective of the influence of Eurasian snow cover.